PENETAPAN DAYA TAMPUNG BEBAN PENCEMAR TUKAD MATI DI KABUPATEN BADUNG DENGAN MODEL QUAL2KW 5.1 - i kadek ardi putra; I Wayan Budiarsa Suyasa; I G B Sila Dharma (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2017)
ABSTRAK Tukad Mati is one of watershed that is flow through two regencies of Badung and Denpasar that has 12 km length. Tukad Mati functioned as irrigation, drainage system and as the exile of wastewater from all activities along the river. Because of the pollution, the water quality has degraded. The source of pollution is organic matter pollutant, agricultural pollutant such as pesticide and hazardous waste. The aim of this research is knowing the pollutant loading rate from point source and non point source using Qual2kw model, to define that amount of pollutant that are allowed to exile in Tukad Mati river. The water quality parameter that analyzed is DO, COD, BOD and Phosphate. This research divided into three sections, and 4 scenario of simulation to know allowed loading rate of pollutant along the river. The result of simulation using Qual2kw for BOD that is the minimum DO loading rate was 1,15 kg/day for section 1 then maximum loading rate is 64,88 kg/day on section 3. Meanwhile for COD parameter, the minimum loading rate is 1446,61 kg/day and in the upstream the minimum COD loading rate 1375,06 kg/day. For phosphate parameter the loading rate that allowed is 0,79 kg/day, while in the upstream maximum 12,57 kg/day on segment 3. Keywrods : Tukad Mati, Qual2KW 5.1, Loading Rate, water quality